(3OjhGf GdHGNQRjs - (3GdHGNQRj , Ydj Hf GdMSf Hf Ydj Hf CHj GdWjH, CHh GdMSf,J (B467 (3g` s
(3ChdgG (B:s
(3YTfG Edi Cf QCjfG aj Gdghi YLHkG cd GdTghQ haj GdCeKGd YT QLHkG s
(3BNQgG (B:s
(3ef bUjOI gGFjI(B: (3EPG NQW GdjGbhJ aUkG dNGJe adG JYLHhG dh PG HZjVkG NW gPg s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B81s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B34 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B778s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdCOHs